320 Effect of accumulated unhealthy behaviors on insomniaâ€lifestyle-related disease differences in a Japanese community population. (3rd May 2021) - Kato, Suzuka; Harada, Sei; Iida, Miho; Kuwabara, Kazuyo; Sugiyama, Daisuke; Takeuchi, Ayano; Hirata, Aya; Sata, Mizuki; Matsumoto, Minako; Kurihara, Ayako; Okamura, Tomonori; Takebayashi, Toru
Abstract: Introduction: Some studies reported that health behaviors and lifestyles are related to sleep disorder; obesity, drinking, smoking and lack of physical exercise are risk factors for insomnia. However, it's unclear the association between accumulated unhealthy behaviors and insomnia in consideration of lifestyle-related diseases. Therefore, this study was to examine the effect of accumulated unhealthy behaviors on insomnia in a Japanese community population. Methods: The subjects included 1, 1002 participants aged 35–74 years. Sleep quality was assessed by the Athens Insomnia Scale. Unhealthy behaviors were classified into smoking, drinking, no habit of exercising, obesity, and skipping breakfast. We examined the impact of unhealthy behaviors accumulation, which was stratified into three categories, i.e., 0-1, 2-3, 4 or more, on insomnia. The association between accumulated unhealthy behaviors and insomnia was estimated by logistic regression analysis. Further analysis after stratification by lifestyle-related diseases was also performed. Results: The overall prevalence of insomnia was 14.6% for men and19.3% for women. Men with unhealthy behaviors were more likely to have insomnia after adjusting for potential confounders, compared with the least unhealthy groups (trend p=0.017). Women with 4 or more unhealthy behavior factors were more likely to have the suspected insomnia, compared with the lowest groups (ORs 1.176 95% CI 1.079–1.282). Then, we analyzed to stratify by lifestyle-related disease. Insomnia has an association with unhealthy behaviors among men with the absence of diabetes (trend p=0.015) and dyslipidemia (trend p=0.032). Women without hypertension were more likely to have the suspected insomnia, compared with the lowest groups (ORs 1.215 95% CI 1.102–1.340), but the odd for those with the hypertension was 1.031(95%CI 0.855–1.243). Conclusion: Accumulated unhealthy behaviors were associated with increased rates of insomnia in the Japanese community population. According to stratification by lifestyle-related disease, men showed the associations by the presence or absence of diabetes. Women showed the associations by the absence of hypertension. These associations were nearly similar regardless of the presence or absence of lifestyle-related disease. Support (if any): This research was supported by research funds from the Yamagata Prefectural Government and the city of Tsuruoka and the Grant-in-Aid for Scientific Research (JP24390168, JP15H04778 and JP19K19441) from the Japan Society for the Promotion of Science.